A new species of Polypoetes Druce, 1885 (Lepidoptera: Notodontidae) from Colombia, with confirmation of a new host plant for the Dioptinae - Ryan A. St Laurent (Revista Chilena de Entomología, 2023)
A new species of the genus Polypoetes Druce, 1885, Polypoetes milleri spec. nov. from Colombia is described. We provide diagnostic characters for the species, photographs of the adults and genital structures of both sexes. Additionally, we confirm a new host plant for the subfamily Dioptinae, Quararibea cordata (Malvaceae), commonly known as “zapote”.